Cytotoxicity study of homopolymers and copolymers of 2-hydroxyethyl methacrylate and some alkyl acrylates for potential use as temporary skin substitutes - Prasitsilp M. (2014)
The cytotoxicities of both homopolymers and copolymers of 2-hydroxyethyl methacrylate (HEMA) and various alkyl acrylates (AA) were investigated using cell culture techniques. The particular alkyl acrylates used were methyl acrylate (MA), ethyl acrylate (EA) and butyl acrylate (BA). The AA contents of the polymers studied were in the range of 0-25% by weight. They were synthesized via bulk polymerization in the form of thin sheets of 0.5 ± 0.1 mm thickness. After sterilization using ethylene oxide gas, cytotoxicity tests, including both direct and indirect contact tests, were performed using cell lines of L929 and normal human dermal fibroblasts. The results showed that P(HEMA-co-EA) with EA contents of 15-25% and P(HEMA-co-BA) with BA contents of 10-25% appeared to be non-cytotoxic and attractive for more specific cytocompatibility tests and in vivo studies with a view to their use as temporary skin substitutes. © 2003 Kluwer Academic Publishers.